A novel infinite-acting radial-flow analysis procedure for estimating horizontal and vertical permeability from an observation-probe pressure response - Onur, M. (European Association of Geoscientists and Engineers, EAGE, 2013)
This paper presents a new infinite-acting radial-flow analysis procedure for estimating horizontal and vertical permeability solely from pressure transient data acquired at an observation probe during an interval pressure transient test (IPTT) conducted with a single-probe or dual-packer module. The procedure is based on new infinite-acting radial-flow equations that apply for all inclination angles of the wellbore in a single-layer, 3D anisotropic, homogeneous porous medium. The equations for 2D anisotropic cases are also presented and are derived from the general equations given for the 3D anisotropic case. It is shown that the radial-flow equation presented reduces to the Prats' equation assuming infinite-acting radial flow at an observation point along a vertical wellbore in isotropic or 2D anisotropic formations of finite bed thickness. The applicability of the analysis procedure is demonstrated by considering synthetic and field probe-probe and packerprobe IPTT data. The results indicate that the procedure provides reliable estimates of horizontal and vertical permeability solely from observation-probe pressure data during radial flow for vertical, horizontal, and slanted wellbores. Most importantly, the analysis does not require that both spherical and radial flow prevail at the observation probe during the test. Copyright 2013, Society of Petroleum Engineers.